1993
DOI: 10.1002/mrd.1080340308
|View full text |Cite
|
Sign up to set email alerts
|

Human sperm–egg binding is inhibited by peptides corresponding to core region of an acrosomal serine protease inhibitor

Abstract: An antiserum, designated R4 and raised against denatured hamster acrosomes, was shown to localize specifically to the acrosomal region of hamster, rat, mouse, and human spermatozoa, and to inhibit both hamster and human sperm-oocyte binding in vitro. Following screening of a human testis lambda gt11 cDNA expression library with the antiserum R4, a series of cDNA clones were isolated. One (cDNA 134) was selected based on the ability of the beta-galactosidase fusion protein to inhibit human and hamster sperm-zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
37
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 42 publications
0
37
1
Order By: Relevance
“…Plasma PCI seems to be produced mainly in the liver because the plasma level of PCI decreased in patients with severe liver diseases (14). Recently, PCI was detected in human seminal plasma, Graaf follicular fluid, testis, epididymis, prostate, seminal vesicle (15), and the preacrosomal region of human spermatozoa (16,17). PCI was found previously to inhibit acrosin, a serine protease localized in the acrosome of spermatozoa (17,18).…”
Section: ؊1 ⅐Minmentioning
confidence: 99%
“…Plasma PCI seems to be produced mainly in the liver because the plasma level of PCI decreased in patients with severe liver diseases (14). Recently, PCI was detected in human seminal plasma, Graaf follicular fluid, testis, epididymis, prostate, seminal vesicle (15), and the preacrosomal region of human spermatozoa (16,17). PCI was found previously to inhibit acrosin, a serine protease localized in the acrosome of spermatozoa (17,18).…”
Section: ؊1 ⅐Minmentioning
confidence: 99%
“…In humans, PCI is expressed in different organs and tissues; the highest PCI concentration occurs in seminal plasma (11) and in seminal vesicle secretions (12). The PCI has also been shown to be present in the testis and the prostate and on the acrosomal cap of human sperm (13). Some studies have also suggested that PCI could play a role in male fertility (reviewed in Ref.…”
mentioning
confidence: 96%
“…Interestingly, the level of seminal plasma PCI was found to be low in some infertile men 115, 161. In contrast, PCI was also reported to inhibit the serine protease acrosin [19], present in the acrosome of spermatozoa as well as the binding of the spermatozoa to oocytes [17], suggesting a potential role for PCI in the regulation of fertilization.Ejaculated human semen is composed of seminal vesicle secretion (seminal fluid), prostatic fluid, and epididymal fluid containing the spermatozoa. The seminal fluid is composed of a gelatinous coagula containing two major proteins, semenogelins I (Sg I, 52 kDa) and 11 (Sg 11, 71-76 kDa).…”
mentioning
confidence: 99%
“…Interestingly, the level of seminal plasma PCI was found to be low in some infertile men 115, 161. In contrast, PCI was also reported to inhibit the serine protease acrosin [19], present in the acrosome of spermatozoa as well as the binding of the spermatozoa to oocytes [17], suggesting a potential role for PCI in the regulation of fertilization.…”
mentioning
confidence: 99%
See 1 more Smart Citation